Tinjauan Pustaka Pengembangan Desain Mata Punch pada Proses Punching Multi Plate Pipe - Naufal Eka Prasetya; Dan Mugisidi (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
The multi-plate pipe punching process is a crucial manufacturing technology in modern industry, especially in the manufacture of high-precision perforated pipe components. This study aims to examine the development of an optimal punch eye design to improve efficiency and product quality in the multi-plate pipe punching process. The method applied in this research is descriptive literature analysis by reviewing various relevant reference sources on punch design, materials, and punching process parameters. The results show that the optimal punch design must consider geometric factors, material selection, cooling systems, and wear analysis. Material innovations such as tool steel with high alloy steel and special coatings have been proven to increase service life. Finite Element Analysis (FEA) simulation is an effective tool for design optimization prior to actual implementation. This study provides punch eye design recommendations that can be practically applied in the manufacturing industry to increase productivity and reduce production costs.